Peran Tata Usaha Dalam Pengelolaan Arsip Di Sekolah Menengah Kejuruan (SMK) Swasta Gebang - Dhea Alwina; Usmaidar Usmaidar; Ahmad Zaki (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This research is entitled The Role of Administration in Archives Management in Gebang Private Vocational High School (SMK). The formulation of the problem in this study include: how is the role of administration in the management of school archives in Gebang Private Vocational School, Gebang District and how are the obstacles faced in managing school archives at Gebang Private Vocational School in Gebang District and the solutions. The expected benefits of this research include: adding insight and knowledge, especially in the field of education and knowing how the role of the administrative section in managing school archives at the Gebang Private Vocational School, Gebang District with the actual conditions in the field. This research uses the Field Research research method (field research) using a descriptive qualitative research approach. The research results obtained in this study include: The role of administration in the management of school archives is very good. The role of school administration includes, firstly, the head of administration as the person in charge of administrative operations in charge of coordinating all administrative activities, serving, assisting, and fulfilling or providing matters relating to educational information in schools. Second, is as a school education staff. The head of administration is very competent in his field and is responsible for his duties. The head of administration is already professional in carrying out his duties in the administrative section so that it is much more effective. In terms of staff development, school principals and administrative heads of Gebang Private Vocational Schools have done various things, namely involving staff in activities, such as training, upgrading, seminars and workshops. The most important administrative role is as an educational staff and as a provider of information regarding the management of records in schools, as well as being able to work together with all staff in preparing plans for managing school records. The problems that exist in the administrative section in managing school archives at Gebang Private Vocational Schools, first, lack of facilities and infrastructure for archive storage because the number of archives is increasing continuously. Second, schools use a lot of non-permanent education personnel. As has been explained, the head of school administration is the one who helps carry out the main work to achieve school goals. The solution needed from problems in managing school archives is first, by carrying out maintenance and prevention of damage to archive storage devices. secondly, the required facilities must have met the requirements, such as a large room, complete archive storage equipment and sufficient for storage of archives that are increasing in volume from time to time. third, the staff who manages the archives have met the requirements so that they are responsible for carrying out their work in accordance with their respective duties.